BENTUK TES OBJEKTIF DAN KECEMASAN PADA PEMBELAJARAN MEMBACA HURUF HIRAGANA BAHASA JEPANG - Kartika Sakti Oktaviani (Jurnal Evaluasi Pendidikan, 2017)
This research aims to see the effect of objective tests and Japanese language anxiety toward the hiragana reading achievement in Japanese language. The form of the test includes multiple choice form and true false form of objective tests. Japanese language anxiety includes low and high anxiety. The method of research is an experimental method. While the design of research uses treatment by level 2 x 2. The hypothesis of research were tested by using two-way analysis of variance (ANAVA).The result of research concluded that: (1) The hiragana reading achievement in Japanese language of students who were given multiple choice form of the formative tests is higher than achievement of students reading hiragana Japanese language students who were given a true false test, (2) There is an influence of objective test form and Japanese language anxiety towards the achievement of hiragana reading in Japanese language, (3) For group of students with low Japanese language anxiety, the achievement of the group of students who were given multiple choice of objective tests is higher than the achievement of reading hiragana Japanese language students group who were given a true false of objective tests, and (4) For group of students with high Japanese language anxiety, the achievement of the group of students who were given multiple choice of objective tests is lower than the achievement of hiragana reading in Japanese language of students group given a true false of objective tests.